Evaluation of the ventro 20° rostral‐dorsocaudal oblique radiographic projection for the investigation of canine nasal disease. (26th May 2015) - Finck, M.; Durand, A.; Hammond, G.; Sullivan, M.; King, A.
<x xml:space="preserve">Abstract</x> OBJECTIVE To assess the ventro 20° rostral‐dorsocaudal oblique projection for canine nasal disease as an alternative to the dorsoventral intra‐oral view. MATERIALS AND METHODS Thirty‐one dogs with nasal disease underwent radiography and computed tomography with a final diagnosis of underlying cause achieved through rhinoscopy, biopsy or cytology. Three independent observers, blinded to diagnosis, reviewed the nasal radiographs on two separate occasions. Intra‐ and inter‐observer agreement and level of confidence on radiographic diagnosis were evaluated and radiographic diagnosis was compared with computed tomography and definitive diagnosis. RESULTS The ventro 20° rostral‐dorsocaudal oblique projection of canine nasal cavities was feasible in anaesthetised dogs and gave diagnostic quality images in most dogs. Assessment of this view showed moderate to substantial agreement with computed tomography diagnosis but gave lower confidence in diagnosis. Interpretation of this radiographic projection had substantial to almost perfect repeatability but moderate reproducibility. CLINICAL SIGNIFICANCE The ventro 20° rostral‐dorsocaudal oblique projection may be used as a valuable initial screening tool for canine nasal pathology in practices without access to advanced imaging, although computed tomography is still likely to provide greater diagnostic information.